Analisis Masalah Pengembangan Perbankan Syariah di Indonesia: Aplikasi Metode Analytic Network Process - Aam Slamet Rusydiana (Esensi: Jurnal Bisnis dan Manajemen, 2016)
The Development Problems Analysis of Islamic Banking in Indonesia: Application Analytic Network Process MethodThis study would try to address the problems that faced by Islamic banking institutions in Indonesia. The results showed that the problems that arise in the development of Islamic banks in Indonesia consists of four important aspects, namely: human, technical, legal/structural aspect, and market/communal aspect. Decomposition of problem as a whole gains the priorities: 1) There is not enough of Islamic banks capital yet; 2) Lack of understanding of Islamic bank practitioners; 3) Lack of government support; 4) the trust and public interest to Islamic banks tend to be low.While the priority of policy strategies that are considered able to resolve the problems of Islamic banking industry in Indonesia consists of: 1) strengthen the capital and business scale and improve the efficiency level; 2) improve the quantity and quality of human resources, and also information systems and technologies; Furthermore, 3) improve the structure of Islamic bank funds and harmonization of regulation and supervision. DOI: 10.15408/ess.v6i2.3573